Food Legumes: Physicochemical and Nutritional Properties - Amarowicz, Ryszard (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This new MDPI book should be of interest to a wide range of readers. Students of a variety of faculties, employees of the food industry, producers of functional food, farmers, and nutritionists will certainly be interested. The book provides new information on legumes, their nutritional value, the content of biologically active compounds, and changes in the activity of these compounds as a result of the application of various technological processes. The book will not only increase the knowledge of readers but also potentially motivate them to change their diets by including legumes on the menu. According to nutritionists' recommendations, such a change has a positive effect on health.